Graphical Representation: a heuristic-didactic resource for the teaching-learning of Mathematics |: Representación Gráfica: recurso heurístico-didáctico para la enseñanza-aprendizaje de la Matemática - Bermudo Navarrete, Sergio (2024)
The limitations and difficulties presented by students in the learning of Mathematics highlight the need to provide teachers with strategies to favor the teaching-learning process of Mathematics. In this direction, a didactic strategy is proposed to take advantage of the potential of Graphic Representation as a heuristic-didactic resource in the teaching-learning process of Mathematics.